A review of the relationship between mental health, wellbeing and drought resilience in rural, regional and remote communities - Emma K. Austin; Anthony S. Kiem (Frontiers in Psychiatry)
Rural, regional and remote communities are vulnerable to the impacts of drought due to their reliance on agriculture, water intensive industries and nature-based tourism. These communities experience significant environmental, social, economic and health impacts because of the reoccurring nature of droughts. This paper reviews the literature on the relationship between mental health, wellbeing and drought resilience and finds that increasingly, mental health and wellbeing are being addressed through a range of drought resilience interventions as it is recognised that good (poor) mental health and wellbeing is linked to high (low) drought resilience. This is because improving mental health and wellbeing increases adaptive capacity and high adaptive capacity is necessary for high drought resilience. Despite this recent progress it is also recognised that there is a lack of tools and resources that (a) recognise when people need help and (b) efficiently connect people to help that is available at the time the help is required. These findings will inform the development of an online rural wellbeing toolkit aimed at enhancing mental health and wellbeing in order to improve drought-resilience in rural, regional and remote Australian communities.